WOMEN, FOOTBALL AND EUROPEAN INTEGRATION. AIMS AND QUESTIONS, METHODOLOGICAL AND THEORETICAL APPROACHES - Pfister, Gertrud (Annales Kinesiologiae, 2013)
<span style="line-height: 150%; font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The aim of this article is to introduce a new research topic and provide information about a European research project focusing on football as a means of European integration. Using the results of available studies of the author and other scholars, it is to be discussed whether and how women can participate in football cultures and contribute to a European identity. Based on theoretical approaches to national identity, gender and socialization, as well as and on the analysis of various intersections between gender, football and fandom, it can be concluded that women are still outsiders in the world of football and that it is doubtful whether female players and fans will contribute decisively to Europeanization processes.